On the importance of tetrel bonding interactions in lead(ii) complexes with (iso)nicotinohydrazide based ligands and several anions. Issue 26 (9th June 2016) - Mahmoudi, Ghodrat; Bauzá, Antonio; Amini, Mojtaba; Molins, Elies; Mague, Joel T.; Frontera, Antonio
Abstract : We report four Pb(ii ) complexes with (iso)nicotinohydrazide based ligands exhibiting relevant tetrel bonding interactions that have been characterized using DFT calculations. Abstract : Four Pb(ii ) complexes of (iso)nicotinohydrazide-based ligands and different anionic coligands (azide, nitrate, acetate and iodide) have been synthesized and characterized by structural, analytical and spectroscopic methods. The mono-deprotonated or neutral forms of the ligands coordinate in a tridentate fashion via two nitrogen and one oxygen donor atoms to the Pb. Single-crystal X-ray crystallography showed that the molecular complexes can aggregate into larger entities depending upon the anion coordinated to the metal centre. In all four complexes the lead center is hemidirectionally coordinated and, consequently, it is sterically ideal for establishing tetrel bonding interactions. In the crystal structures of all complexes, the lead atoms participate in short contacts with nitrogen atoms. These contacts are shorter than the sums of the van der Waals radii and larger than the sums of the covalent radii. The tetrel bonding interactions interconnect the covalently bonded units (monomers or dimers) into supramolecular assemblies (chains and 3D structures). We have analysed the interesting supramolecular assemblies observed in the solid state of all four complexes by means of DFT calculations.